2009
DOI: 10.1177/1933719109343787
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Human Umbilical Artery Contractility By Different Serotonin and Histamine Receptors

Abstract: We studied the role of several serotonin (5-HT) and histamine receptors in the regulation of human umbilical artery (HUA) contractility. Among the 5-HT agonists used, only the 5-HT( 2A) and 5HT(1B/D) agonists contracts HUA. The 5-HT-induced contractions were fully inhibited by ketanserin (5-HT(2A) antagonist). The 5-HT( 7)-activation also relaxes and increases intracellular cyclic adenosine monophosphate (cAMP). Among the histamine receptor agonists, only betahistine (H(1) agonist) induced significant contract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…Fittingly, none of the groups presented in this study happened to show a significant impact on normalized cochlear blood flow. However, it has also been shown that betahistine has a direct effect on vessels [Laurikainen et al, 1998;Santos-Silva et al, 2009]. In addition to that, a study conducted by this workgroup managed to show a significant increase of cochlear blood flow caused by the infusion of aminoethylpyridine, a product of betahistine metabolism [Bertlich et al, 2014].…”
Section: Discussionmentioning
confidence: 95%
“…Fittingly, none of the groups presented in this study happened to show a significant impact on normalized cochlear blood flow. However, it has also been shown that betahistine has a direct effect on vessels [Laurikainen et al, 1998;Santos-Silva et al, 2009]. In addition to that, a study conducted by this workgroup managed to show a significant increase of cochlear blood flow caused by the infusion of aminoethylpyridine, a product of betahistine metabolism [Bertlich et al, 2014].…”
Section: Discussionmentioning
confidence: 95%
“…In the case of His, the contraction is achieved by the activation of the H 1 receptors, which is coupled to a Gq protein, that activates the PLC/IP 3 signaling cascade, leading to an intracellular increase of Ca 2+ …”
Section: Physiological Regulation Of Hua Contractilitymentioning
confidence: 99%
“…However, the HUA smooth muscle also expresses another 5‐HT receptor (5‐HT 7 ) and two other receptors of His (H 2 and H 3 ) that are associated with a Gs protein. The activation of these receptors stimulates adenyl cyclase and leads to vasorelaxation …”
Section: Physiological Regulation Of Hua Contractilitymentioning
confidence: 99%
See 1 more Smart Citation
“…SSRIs, and some other antidepressants, act on the crucial serotonin transporter (SERT, aka 5HTT, SLC6A4, OMIM 182138), which regulates the synaptic concentration of serotonin (5HT) in many tissues, including the placenta[7]. The resultant increased bioavailability of serotonin affects vasoconstriction and coagulation or bruising [6,8,9], cardiac morphogenesis [10,11], CNS development[6] gastrulation, laterality and craniofacial development[10], conferring biological plausibility on reported associations between SSRI exposure during organogenesis and certain congenital anomalies.…”
Section: Introductionmentioning
confidence: 99%